Визначення ефективності оброблення сортівки вуглецевим активованим та модифікованим матеріалом - Самченко, Ірина Олександрівна; Олійник, Світлана Іванівна (My University, 2020)
Досліджено ступінь очищення водно-спиртової суміші та підтверджено підвищення дегустаційної оцінки та окиснюваності сортівки після її обробки вуглецевим активованим та модифікованим матеріалами, що вказує на видалення з неї небажаних органічних мікродомішок. Проведено порівняння показників якості сортівки, приготованої на різних сортах спирту етилового ректифікованого до та після її очищення. Встановлено, що лужність сортівки, очищеної активованим вуглецевим волокном та активованим вуглецевим модифікованим волокном, збільшується у 1,16 рази і є меншою ніж під час застосування контрольного зразка. Визначено, що оптимальніше співвідношення поверхневих оксидів основного та кислотного характеру сприяє меншій каталітичній активності досліджуваних матеріалів і підтверджується меншим збільшенням масової концентрації в безводному спирті. Під час використання активованого вуглецевого модифікованого волокна спостерігали досягнення максимальної прозорості очищеної сортівки. Про вищу ефективність застосування вуглецевого активованого модифікованого матеріалу свідчить вища різниця за окиснюваністю до та після очищення сортівки. Показано, що обробка досліджуваними матеріалами є перспективною для додаткового очищення сортівки без застосування додаткового обладнання. The degree of purification of the water-alcohol mixture was investigated and the increase of tasting evaluation and oxidizability of the sorting after its treatment with carbon activated and modified materials was confirmed, which indicates the removal of unwanted organic micro-impurities from it. The comparison of quality indicators of sorting prepared on different grades of rectified ethyl alcohol before and after its purification is carried out. It was found that the alkalinity of the grade purified with activated carbon fiber and activated carbon modified fiber increases by 1,16 times and is less than when using the control sample. It is determined that the optimal ratio of surface oxides of basic and acidic nature contributes to lower catalytic activity of the investigated materials and is confirmed by a smaller increase in mass concentration in anhydrous alcohol. When using activated carbon modified fiber, the achievement of maximum transparency of the purified grade was observed. The higher efficiency of application of carbon activated modified material is evidenced by the higher difference in oxidation before and after cleaning the sort. It is shown that the treatment of the investigated materials is promising for additional cleaning of the sort without the use of additional equipment. The transparency of the initial water-alcohol mixture is improved up to 20 times during cleaning by the investigated materials and reaches the values regulated by the national standard, while the maximum possible transparency is sorted, which was cleaned with activated and modified carbon fiber The reduction of harmful organic micro-impurities in the water-alcohol mixture after its purification by the studied carbon fiber materials indicates the efficiency of processing by 70 - 87%, and is confirmed by the improvement of the overall tasting score by 0,3 points when using activated and modified carbon fiber and 0,2 points for activated carbon fiber.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; вуглецеве активоване та модифіковане волокно; виробництво горілок; сортівка; ефективність; очищення; activated carbon modified fiber; production of vodka; sorting; cleaning efficiency